The Treaty of Lisbon: changing perceptions through redenomination - Fernandes, Maria Fernanda (2018)
The European Union (EU) has been plagued by a democratic deficit (Meyer, 1999) and by the need to justify the European integration (Glencross, 2009). These authors, among others, have put the lack and/or the failure of political communication as central to the debate. The 2004 Treaty Establishing a Constitution for Europe (TCE) initiated a period of great changes in the integration project since it was an important step in formalizing the conceptual entity that is the EU. The unsuccessful task of explaining and (in)forming citizens on the notion of a constitutional treaty is reflected in the increasing fears among several of its member states regarding the ensuing loss of political power, and consequently, even greater loss of national sovereignty.